Decoding the role of encapsulated ions in the electronic and magnetic properties of mixed-valence polyoxovanadate capsules X@V22O54 (X = ClO4−, SCN−, VO2F2−): a combined theoretical approach. Issue 26 (20th June 2018) - Notario-Estévez, Almudena; Kozłowski, Piotr; Linnenberg, Oliver; de Graaf, Coen; López, Xavier; Monakhov, Kirill Yu.
Abstract : The magnetic states of polyoxovanadate host cages respond to inclusion of diamagnetic guest ions. Abstract : The electronic structure and magnetism of mixed-valence, host–guest polyoxovanadates {X@VIV/V22O54 } with diamagnetic (X =) ClO4 − ( T d, 1 ) and SCN − ( C ∞v, 2 ) template anions are assessed by means of two theoretical methods: density functional theory and effective Hamiltonian calculations. The results are compared to those obtained for another member of this family with X = VO2 F2 − ( C 2v, 3 ) (see P. Kozłowski et al., Phys. Chem. Chem. Phys., 2017, 19, 29767–29771), for which complementary data are also acquired. It is demonstrated that the X guest anions strongly influence the electronic and magnetic properties of the system, leading to various valence states of vanadium and modifying V–O–V exchange interactions. Our findings are concordant with and elucidate the available experimental data (see K. Y. Monakhov et al., Chem. – Eur. J., 2015, 21, 2387–2397).